Implementation of Character Education Programs in Instilling an Attitude of Tolerance - Hermawan, Dani; Azizah, Shintya Ajeng Guswan (Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2023)
Intolerance in Indonesia is currently a problem that is quite worrying for the community and also for the government, as many people know that Indonesia has very diverse religions and cultures, so institutions are required to implement character education programs to instill tolerance from an early age so that the next generation can instill a spirit of tolerance. One day, they will be able to implement it properly. Instilling the values of solidarity and inter-religious harmony through education is an effective and appropriate way, so it is necessary to implement a Character Education Program to instill tolerance. This research aims to describe how to implement character education programs in instilling an attitude of tolerance and what the factors are in it. It uses a case study of qualitative approaches. The results are (1) Implementation of the character education program in instilling an attitude of tolerance includes three stages, namely, planning, action, and evaluation, and (2) Supporting factors include motivation from the family environment, which is very influential, and school facilities such as posters, pictures, etc., inhibiting factors include: differences in students' character backgrounds and attitudes which can disrupt the course of learning.